The opaque-2 mutation of maize differentially reduces zein gene transcription. - Kodrzycki, R (1989)
Zeins, the storage proteins of maize seed, are encoded by a large multigene family that is regulated developmentally and expressed in a tissue-specific manner during endosperm development. The synthesis of these proteins is affected by mutations, such as opaque-2, that cause a reduction in the accumulation of zein proteins and mRNAs. We used nuclear run-on transcription assays to analyze the expression of zein genes in developing normal and opaque-2 endosperms and to map the origin of these transcripts with respect to the coding and noncoding regions of the genes. These analyses demonstrate that zein gene expression is regulated transcriptionally and posttranscriptionally in developing endosperm. Transcription of genes encoding alpha-zeins is inhibited significantly in opaque-2 mutants, with expression of those encoding the M(r) 22,000 proteins being almost totally blocked. Other gene subfamilies were affected but to a lesser extent.